Pengaruh Pembelajaran Mata Kuliah Manajemen Keuangan, Literasi Keuangan, dan Herding Behavior Terhadap Keputusan Investasi Saham Mahasiswa di Kota Surabaya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of financial management learning, financial literacy, and herding behavior on students’ stock investment decisions in Surabaya. This research uses a quantitative approach with purposive sampling technique. Data were collected through questionnaires distributed to university students who have taken financial management courses and are involved in stock investment activities. The data analysis technique employed is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that financial management learning and financial literacy have a positive and significant effect on students’ stock investment decisions, as they enhance knowledge and analytical skills in decision-making. Meanwhile, herding behavior also influences investment decisions, reflecting students’ tendency to follow group behavior in investing. In conclusion, both financial knowledge and psychological factors play important roles in shaping students’ investment decisions. Therefore, improving the quality of financial education and financial literacy is essential to encourage more rational investment decision-making